(untitled) (Bangladesh Journal of Agricultural Research, 2016)
The experiment on papaya (Carica papaya L.) consisting of fourteen genotypes from diversd gene pool was conducted at the Regional Agricultural Research Station, Ishurdi, Pabna during April 2013 to May 2014 to study the nature and magnitude of genetic divergence and eventually identification of suitable genotypes for use in breeding program. Multivariate analysis was subjected to assess the genetic diversity and Mahalanobis generalized distance (D2) was used to assess the divergence present among the genotypes. The fourteen genotypes were grouped into four clusters. The cluster IV had the maximum genotypes (5) followed by cluster I having 4 genotypes and cluster II having 3 genotypes. Cluster III had the minimum genotypes (2). The inter-cluster distances were greater than intra-cluster distances in all cases, suggesting wider genetic diversity among the genotypes of different groups. The highest intracluster distance was observed in cluster III and the lowest in cluster II. The maximum inter-cluster distance was estimated between clusters I and IV (11.3212), moderate distance between clusters II and IV (9.961) and clusters III and IV (7.568), and that of the lowest between clusters I and III. Cluster III recorded the highest mean values for fruit length, plant height at last harvest, number of fruits/plant, weight of fruits/plant and fruit yield, while cluster IV exhibited the maximum mean values for pulp thickness, plant height at 1st harvest and the second highest mean values for fruit length, fruit breadth and TSS. Therefore, more emphasis should be given on cluster III for selecting genotypes as parents for crossing with the genotypes of cluster IV which may produce new recombinants with desired traits. Bangladesh J. Agril. Res. 41(4): 647-656, December 2016